Sensor enhanced rehabilitation for knee injuries / Shirana Asmi Farook, Tan Wei Xiang and N. Yogadarrshini - Farook, Shirana Asmi; Tan, Wei Xiang; N, Yogadarrshini (Universiti Teknologi MARA, Kedah, 2019)
Knee injuries or knee pathologies are common among normal population and athletes and were frequently presented in general clinical practice. Muscle activity and muscle strength is important in knee rehabilitation and the physiotherapist’s understanding of how and what muscles move during various activities and exercises can enhance them to apply different strength training procedures, specific group muscle protocols and choose more efficient and secure methods for exercising which helps in injury rehabilitation. At present muscle monitoring during rehabilitation is largely restricted to laboratory setup and not feasible for long term monitoring under real life conditions and existing approaches such as EMG, require bulky hardware or special attachment of leaded electrodes to the skin , making wide spread placement difficult. In the Physiotherapy clinical setting, it is difficult to evaluate muscle participation when a patient is performing dynamic functional activities for precise muscle group strength protocol for better and faster recovery, Physiotherapists’ conventional clinical assessments are usually subjective and involve clinician or patient-rated scales for conclusive physiotherapy protocol. Idea/ Propose solution In recent few years, the technology had grown vastly and muscle sensors are introduced. Muscle sensors are able to function like a mini storage device and the muscle activity sensed can be stored in it, which can then be intergraded into readable format. Through this study, our aim is to establish a portable sensor based motion capture system during a variety of clinical functional tasks and custom written program that processes sensor data and generates user friendly clinical movement muscle analysis. In certain injuries, the activities of certain group of muscles will be diminished and by measuring the muscle activities, the affected muscle group will be detected. The therapist can then plan out a better strengthening protocol for the affected group of muscles.